Simulation and testing of flat rolled aluminum plates 6063 - Robert, T; Vázquez, O; López, E (Nexo Revista Científica, 2011)
An experimental methodology was generated for understanding the theoretical and practical concepts inherent to cold flat rolling. Aluminium slabs about 100 mm length, 9 mm thickness with different widths: 10 and 30 mm were rolled. A constant 0.3 mm thickness reduction step was performed in order to achieve a thickness reduction greater than 80 %. In the Abaqus® commercial software, a mathematical model was implemented in order to obtain a greater understanding concerning how the process variables affect the fields of stresses and strains that are not observed experimentally. It was found, by mathematical simulation, that a superficial hardening in the plates was produced and the deformation obtained is heterogeneous, which is corroborated physically. Keywords: Flat rolling; 6063 Aluminium; Data acquisition system; Simulation DOI: http://dx.doi.org/10.5377/nexo.v24i1.594 Nexo, Vol. 24, No. 1, pp. 50-60, 2011